TATA KELOLA LINGKUNGAN IBU KOTA NUSANTARA BERBASIS ILMU FALAK, ECO-ASTRONOMY DAN MAQASHID SYARI’AH - Vivit Fitriyanti; Akhmad Haries (Universitas Nurul Jadid, 2026)
This study examines the scope of applying Islamic astronomy (Ilmu Falak), eco-astronomy, and Maqasid al-Shari’ah within the environmental governance framework of Ibu Kota Nusantara (IKN), focusing on their contribution to sustainable urban development. It aims to identify the benefits of astronomical science in environmental planning, explore its potential to support sustainability, analyze challenges and opportunities for policy integration, and formulate data-driven recommendations aligned with ecological principles. The research employs a descriptive qualitative method using interdisciplinary approaches drawn from Ilmu Falak, eco-astronomy, and Maqasid al-Shari’ah. The findings reveal three major contributions. First, astronomical calculations can guide the accurate determination of qibla orientation for mosques, prayer rooms, public buildings, and Muslim cemeteries in IKN; optimize solar trajectory mapping for energy efficiency; and support disaster mitigation related to lunar and terrestrial cycles. Second, eco-astronomy principles can be implemented through the establishment of a national dark-sky conservation zone for astronomical research and ecosystem protection, environmentally responsible lighting management to enhance energy efficiency, and the development of public education programs—including astro-tourism—to stimulate sustainable economic growth. Third, from the Maqasid perspective, the integration of Ilmu Falak and eco-astronomy fulfills the essential objectives of Shari’ah (daruriyyat), including the protection of religion, life, intellect, wealth, progeny, and the environment. The study recommends the development of technical guidelines, the integration of astronomical data into urban planning systems, and expanded interdisciplinary collaboration. It concludes that combining Islamic astronomy and eco-astronomy with Maqasid values can produce a more adaptive, holistic, and justice-oriented model of environmental governance.